2020
DOI: 10.3390/ijms21197416
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-α Deletion Attenuates Cisplatin Nephrotoxicity by Modulating Renal Organic Transporters MATE-1 and OCT-2

Abstract: Cisplatin is a chemotherapy drug widely used in the treatment of solid tumors. However, nephrotoxicity has been reported in about one-third of patients undergoing cisplatin therapy. Proximal tubules are the main target of cisplatin toxicity and cellular uptake; elimination of this drug can modulate renal damage. Organic transporters play an important role in the transport of cisplatin into the kidney and organic cations transporter 2 (OCT-2) has been shown to be one of the most important transporters to play t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…It is noteworthy that the same pattern of inhibition was observed for An alternative route by which TKIs affect MATE1 function is through effects on transcription factors that result in gene expression changes. Previous studies have suggested a possible role for PPARα [36,37], and basal transcription of the MATE1 gene is regulated by FXR [38] and by binding of Sp1 close to the transcription start site [39], by binding of AP-1/AP2-rep to the promoter region [40], and by Nkx-2.5, SREBF1, and USF-1 [41].…”
Section: Effect Of Tki Treatment On Mate1 Function In Vivomentioning
confidence: 99%
“…It is noteworthy that the same pattern of inhibition was observed for An alternative route by which TKIs affect MATE1 function is through effects on transcription factors that result in gene expression changes. Previous studies have suggested a possible role for PPARα [36,37], and basal transcription of the MATE1 gene is regulated by FXR [38] and by binding of Sp1 close to the transcription start site [39], by binding of AP-1/AP2-rep to the promoter region [40], and by Nkx-2.5, SREBF1, and USF-1 [41].…”
Section: Effect Of Tki Treatment On Mate1 Function In Vivomentioning
confidence: 99%
“…Cisplatin mouse models have been used to investigate pharmacokinetics and tissue distribution of cisplatin [15][16][17], the repair capacity of cisplatin-DNA adducts [18], the molecular mechanisms of cisplatin toxicity [19][20][21][22][23] and to test a new generation of platinumbased chemotherapy drugs or adjunctive therapies [24][25][26][27][28][29][30][31][32][33][34][35], or other potential agents or strategies to prevent or treat cisplatin toxicities [36][37][38][39][40][41].…”
Section: Cisplatin Mouse Modelsmentioning
confidence: 99%
“…Cisplatin is a powerful antineoplastic agent that may induce nephrotoxicity. It causes tubular injury and cell death through multiple mechanisms, including DNA damage, oxidative stress, mitochondrial dysfunction, and inflammation ( 81 , 82 ). Impairment of glucose metabolism has been implicated in cisplatin-induced AKI.…”
Section: Regulation Of Glucose Metabolism In Kidney Diseasesmentioning
confidence: 99%